ANALYSIS OF THE IMPACT OF DIGITAL RUPIAH ON BANKING SYSTEM STABILITY AND MONETARY POLICY EFFECTIVENESS - A’yuni, Meita Qurrrotu; Andika, Muhammad Razif; MustofaMustofa, Haykal; Firmansyah, Muhammad Rayyan; Putri, Sylvia Octa; Adibowo, Rino (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The Digital Rupiah (CBDC) that can potentially be the answer to Indonesia’s financial digitalization struck both opportunities and threats in the national currency ecosystem. Using qualitative methodology, this study investigates regulatory documents, pilot program reports and scholarly articles to ascertain its impact on bank resilience and the efficiency of policy transmission. It is evident that the broad adoption of CBDCs would result in funds shifting out of commercial banks to central bank wallets as liquidity margins are diminished and borrowing costs correspondingly rise. Transparent oversight of transactions gives monetary authorities greater tools to regulate both price levels and credit allocations. The ultimate impact of this instrument, though, depends on whether it’s incentivized with yield that can compete with traditional savings products. This paper presents a governance-oriented framework to motivate well-managed cooperation between monetary authorities and commercial lenders to maintain financial stability in the presence of liquidity shortages.